Ferrite@TiO2-nanocomposites as Z-scheme photocatalysts for CO2 conversion: Insight into the correlation of the Co-Zn metal composition and the catalytic activity. Issue 36 (February 2020) - Ciocarlan, Radu-George; Hoeven, Nick; Irtem, Erdem; Van Acker, Virginia; Mertens, Myrjam; Seftel, Elena M.; Breugelmans, Tom; Cool, Pegie
Graphical abstract: Highlights: Hierarchical Cox Zn1-x Fe2 O4 @TiO2 nanocomposites were successfully synthesized. Strong interconnection was observed between maximum yield of CO and CH4 products and Co/Zn ratio. Selectivity towards CH4 and CO2 was varied by tuning the Co/Zn ratio. Z-scheme mechanism was proven by detailed electrochemistry analyses. Abstract: Photocatalytic conversion of CO2 in the gas phase involving Z-scheme mechanism was studied in the presence of Cox Zn1-x Fe2 O4 @TiO2 (x = 1; 0.2; 0.4; 0.6; 0.8; 0) catalyst nanocomposites. The catalysts were obtained in a two-step approach, consisting of a co-precipitation reaction forming the magnetic Ferrite nanoparticles and a hydrolysis-condensation reaction of the Ti-source forming the titania anatase phase, followed by a calcination procedure. The structural characterization was done by X-ray diffraction, Raman and UV-DR spectroscopy, and physisorption, confirming the presence of both structures in the nanocomposites, with a band gap between 3 and 3.23 eV. In order to determine the CO2 conversion, a photocatalytic gas phase fixed-bed batch reactor in tandem with a GC analyzer were used. The tests were done under UVC light irradiation and CO, CH4 were identified as the main products during photoconversion of CO2 . All the samples showed higher conversions compared to the well-known reference material P25 (Degussa). The CO2 conversion was observed to be directly proportional with the Zn/Co metal ratio in the Ferrite structure, achieving for ZnFe2 O4 @TiO2 ∼50 μmol gcat. -1  h -1 CO and ∼30 μmol gcat. -1  h -1 CH4 . Moreover, for the ZnFe2 O4 @TiO2 catalyst methanol (CH3 OH) formation was observed, while no traces of methanol were detected for the samples containing Co. The electrochemistry analyses clarified the different heterojunctions formed between Ferrites and TiO2 . Mott-Schottky plots revealed the formation of a Z-scheme mechanism for ZnFe2 O4 @TiO2 explaining the best conversion results. On the other hand, the lower activity of CoFe2 O4 @TiO2 was attributed to the formation of a type I heterojunction system.